1997
DOI: 10.1021/js960201u
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Aminopeptidase Activity and Metabolism as Observed in an Organized HaCaT Cell Sheet Model

Abstract: Metabolism studies on organized HaCaT keratinocyte cell sheets are reported. Cells were grown on porous membranes to form organized cell sheets of several cell layers, which were considered as a model of viable epidermis. Metabolism was studied by reflection kinetics, with the top side of the cell sheets in contact with a donor solution and the basal side closed by an impermeable backing layer. Metabolite formation was followed by HPLC of substrate and metabolite in the donor. For comparison, studies with homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In organotypic co-cultures with fibroblasts, conditions that induce normal keratinocytes to form stratified epithelia with all features of a normal epidermis (Smola et al, 1998;Stark et al, 1999), HaCaT cells have been described to be deficient in this complex function of tissue regeneration (Haake and Polakowska, 1993;Syrjänen et al, 1996;Steinsträsser et al, 1997;Boelsma et al, 1999). We have been able to improve their epidermal tissue formation and differentiation in this model by intensifying stromal influences by elevating the number of supporting fibroblasts (Schoop et al, 1999).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In organotypic co-cultures with fibroblasts, conditions that induce normal keratinocytes to form stratified epithelia with all features of a normal epidermis (Smola et al, 1998;Stark et al, 1999), HaCaT cells have been described to be deficient in this complex function of tissue regeneration (Haake and Polakowska, 1993;Syrjänen et al, 1996;Steinsträsser et al, 1997;Boelsma et al, 1999). We have been able to improve their epidermal tissue formation and differentiation in this model by intensifying stromal influences by elevating the number of supporting fibroblasts (Schoop et al, 1999).…”
Section: Discussionmentioning
confidence: 80%
“…This is best demonstrated with the HaCaT cell line, a non-tumorigenic keratinocyte population derived from adult trunk skin exhibiting a rather normal differentiation capacity despite multiple chromosomal alterations (Boukamp et al, 1988;Boukamp et al, 1997;Breitkreutz et al, 1997;Breitkreutz et al, 1998;Ryle et al, 1989). However, organotypic co-cultures of HaCaT cells with skin fibroblasts exhibit some stratification but usually lack typical criteria of an ordered structure and regular keratinization (Haake and Polakowska, 1993;Syrjänen et al, 1996;Steinsträsser et al, 1997;Boelsma et al, 1999). This deficiency, however, was not due to the permanent loss of essential differentiation functions.…”
mentioning
confidence: 99%
“…Samples were analyzed by HPLC for substrate and metabolite as previously described (Steinsträsser et al, 1997). All experiments were run at least in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Values were taken from previously performed independent experiments (Steinsträsser, 1994;Steinsträsser et al, 1997):…”
Section: Theoreticalmentioning
confidence: 99%
“…The drug does not encounter the enzymes inside the cells as it penetrates the skin so that homogenates were not used for this study. It has been shown that homogenates of cells may overestimate the enzymatic activity of the intact cells due to the loss of the organization and compartmentation in homogenates (Steinstrasser et al 1997).…”
Section: Proteolytic Degradation During Skin Transportmentioning
confidence: 99%